2021
DOI: 10.1002/clc.23564
|View full text |Cite
|
Sign up to set email alerts
|

Association between insurance status and in‐hospital outcomes in patients with out‐of‐hospital ventricular fibrillation arrest

Abstract: Background Lack of health insurance is associated with adverse clinical outcomes; however, the association between health insurance status and in‐hospital outcomes after out‐of‐hospital ventricular fibrillation (OHVFA) arrest is unclear. Hypothesis Lack of health insurance is associated with worse in‐hospital outcomes after out‐of‐hospital ventricular fibrillation arrest. Methods From January 2003 to December 2014, hospitalizations with a primary diagnosis of OHVFA in patients ≥18 years of age were extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…We also found a slight decline in the survival trend in both LBH and HBH during the study period in contrast with demonstrated improvement in IHCA survival outcomes over the last 2 decades (23, 24, 27). Lack of health insurance and underinsurance has been linked to higher in-hospital mortality in cardiac arrest patients (8, 30, 31). We only evaluated IHCA patients with Medicaid or no health insurance categorized by safety-net burden across U.S. hospitals, which likely explains the lower survival rates in both LBH and HBH compared with the general population.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a slight decline in the survival trend in both LBH and HBH during the study period in contrast with demonstrated improvement in IHCA survival outcomes over the last 2 decades (23, 24, 27). Lack of health insurance and underinsurance has been linked to higher in-hospital mortality in cardiac arrest patients (8, 30, 31). We only evaluated IHCA patients with Medicaid or no health insurance categorized by safety-net burden across U.S. hospitals, which likely explains the lower survival rates in both LBH and HBH compared with the general population.…”
Section: Discussionmentioning
confidence: 99%